Analyzing the Driving Factors of Purchase Intention at Ayam Goreng Nelongso Restaurant: A Quantitative Study on Customer Experience and Price - Ita Rahmawati; Aldi Kurniawan; Lailatus Sa'adah (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This research was conducted to analyze and determine the influence of customer experience and price on purchase intention at the Ayam Goreng Nelongso restaurant in Jombang. The study employed a quantitative associative method with a causal approach. This causal associative quantitative research aims to assess the extent of the cause-and-effect relationship between customer experience and price on purchase intention. The population targeted in this study includes all customers of the Ayam Goreng Nelongso restaurant, with a sample size of 100 respondents selected through purposive sampling. Data collected via questionnaires were analyzed using statistical tests processed with SPSS version 22. The results of the T-test conducted on both the customer experience and price variables indicate that each significantly influences customers' purchase intention toward the offerings at Ayam Goreng Nelongso. These findings highlight the importance for the restaurant not only to compete on pricing but also to deliver positive sensory and emotional experiences to maintain customer loyalty. Furthermore, the simultaneous test results demonstrate a significant combined effect of customer experience and price on purchase intention, with the F-test showing that the calculated F-value 39.524 > 3.09. Using a significance level of 0.05, the test yielded a p-value of 0.000 > 0.05. The findings confirm that a positive customer experience and fair price perception significantly enhance consumers' intention to purchase.